The Analysis of The Incidence of Depression and Risk of Suicide Using Buddy App on Teenagers in Makassar - Mutmainnah Sari; Arbianingsih Arbianingsih; A. Adriana Amal (Journal of Health Science and Prevention, 2019)
The data from the World Health Organization in 2017, suicidal behavior of teenagers Indonesia of 13-17 years old, as many 5.6% teens had made plans related to the way they committed suicide. The aim of this research is to find out the analysis of the incidence of depression and risk of suicide using Buddy App on teenagers in Makassar. This research was an analytic quantitative with cross-sectional study approach. As many 285 teenagers involved in this research recruited by simple random sampling. Data collected by using a of depression namely KADS that are provided through online form and questionnaire of risk of suicide, namely CSSRS using buddy apps. It is called Buddy App because of its function as an application that can be a close friend to users. The incidence of depression and risk of suicide is higher in the late adolescents. Mean of depression in early adolescent (4.78) and late adolescent (6.31). The statistical test results showed the significant differences between the incidence of depression (p-value 0,000) and the level of risk of suicide (p-value 0,022) in early adolescence and late adolescents. The next researcher is expected to examine the level of depression in each level of suicide risk by developing the questionnaire of depression.